Performing Devotion: Barzanji Recitation as Spiritual Practice Among Arabic Students in Hasanudin University - Muhammad Mahfud Mas'ud; Haeruddin Haeruddin Haeruddin; Haeriyyah Haeriyyah; Sitti Wahidah Masnani (IAIN Palangka Raya, 2025)
Religious ritual practices among the younger generation are declining due to technological advancements, cultural shifts, social changes, and evolving lifestyles. Barzanji, as an oral tradition within Islamic societies, plays a vital role in preserving spiritual and cultural values. Yet, with the diminishing religious ritual engagement among youth, this traditional practice faces preservation challenges. The study aimed to examine the phenomena underlying Barzanji practice among students as a spiritual medium, reflected through their perceptions of the tradition. The subjects, purposively selected undergraduate students from Hasanuddin University's Arabic Literature Department (2021-2024 cohorts), represent future cultural preservation agents as Barzanji practitioners. Data collection employed in-depth interviews, with analysis conducted through data compilation, reduction, and conclusion drawing. Findings reveal that students hold complex perspectives on the relationship between tradition, social identity, and religious values. They perceived the Barzanji tradition not merely as cultural heritage, but as a vital vehicle for character development and spiritual formation. Thus, preserving this tradition necessitates a holistic approach, extending beyond ritual practice to incorporate educational and discursive initiatives that enrich understanding and foster active community-level participation in safeguarding religious rituals.